2017
DOI: 10.1371/journal.pone.0188526
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of processing sentences and compound words in Chinese

Abstract: Sentence reading involves multiple linguistic operations including processing of lexical and compositional semantics, and determining structural and grammatical relationships among words. Previous studies on Indo-European languages have associated left anterior temporal lobe (aTL) and left interior frontal gyrus (IFG) with reading sentences compared to reading unstructured word lists. To examine whether these brain regions are also involved in reading a typologically distinct language with limited morphosyntax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Functional MRI and stereo-EEG studies show that the mental construction of speech chunks is represented in bilateral temporal and frontal lobes ( Ding et al. 2016 ; Bulut et al. 2017 ; Nelson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Functional MRI and stereo-EEG studies show that the mental construction of speech chunks is represented in bilateral temporal and frontal lobes ( Ding et al. 2016 ; Bulut et al. 2017 ; Nelson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Another region where significant functional connectivity was found is the anterior middle temporal gyrus, which significantly coactivated with only LBA45. The anterior temporal lobe has been associated with sentence comprehension in an ALE meta-analysis (Walenski et al, 2019), and several neuroimaging studies implicated this region in combinatorial processing at the sentence level (higher syntactic and compositional semantic processing), usually identified through sentence versus word list contrasts, (Brennan et al, 2012; Brennan & Pylkkänen, 2012; Bulut, Hung, Tzeng, & Wu, 2017; Humphries, Willard, Buchsbaum, & Hickok, 2001; Colin Humphries, Love, Swinney, & Hickok, 2005; Rogalsky & Hickok, 2009). In light of these previous studies and of the behavioral analysis which revealed significant functional specificity in LBA45 only for semantics, it could be argued that functional connectivity between LBA45 and anterior MTG underlies semantic processing, possibly at the sentence level.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if a click is presented during speech, the perceived timing of the click is attracted towards major syntactic boundaries (Fodor and Bever, 1965;Garrett et al, 1966). In terms of the neural basis, fMRI studies have demonstrated that distributed brain areas are involved in grouping words into chunks (Friederici et al, 2000;Lerner et al, 2011;Pallier et al, 2011;Bulut et al, 2017). MEG and EEG studies have suggested that low-frequency neural activity tracks linguistic structures (Ding et al, 2016;Meyer et al, 2016;Martin and Doumas, 2017;Meyer and Gumbert, 2018).…”
Section: Rule-based Chunking Hypothesismentioning
confidence: 99%